Sun Stroke: Physiological Mechanism and Palliative Intervention - Deepak Bhattacharya (Jordan University of Science and Technology, 2023)
Sun stroke the high emergency clinical condition is a cascade of six prominent symptom groups with failed gravity & intramuscular routes; gut constriction; grave prognosis. 2%KCL+5% NaCl +2% CaOH with diluted milk as vector is proposed.  Institutional framework is absent. Nurses are called upon.